Is Subdivision of pT2 Tumors Superior to Lymph Node Metastasis for Predicting Survival of Patients with Gastric Cancer? Review of 224 Patients from Four Centers - DANE, FAYSAL (SPRINGER, 2011)
Background The prognostic significance of the subclassification of pT2 tumors and the association of these categories with other clinicopathological factors in gastric cancer patients were investigated. Methods A total of 224 patients with pT2 gastric cancer who had undergone curative gastrectomy and lymph node dissection were retrospectively analyzed. The prognostic role of the subclassification of pT2 tumors was evaluated by univariate and multivariate analysis. Results Of 224 patients, 75 (33.5%) were classified as having pT2a tumors and 149 (66.5%) as having pT2b tumors. The prevalence of large-sized tumors (P < 0.003), lymph node involvement (P < 0.018), and lymphatic (P = 0.016), blood vessel (P = 0.001), and perineural invasion (P = 0.001) was significantly higher for pT2b tumors than for pT2a tumors. The rate of recurrence for pT2a cancers was significantly lower than that for pT2b cancers (P = 0.001).Median overall survival (OS) times and three-year OS of patients with a pT2b tumor were significantly worse than for patients with a pT2a tumor (P < 0.001).When patients were analyzed according to lymph node involvement, the prognosis of patients with pT2aN(1) cancers was significantly better than that of patients with pT2bN(1) (P < 0.001). Multivariate analysis indicated that the pT2 subdivision was an independent prognostic factor for OS (P = 0.006), as were pN stage, clinical stage, and recurrence. Conclusion Our results showed that subclassification of pT2 tumors into pT2a or pT2b was an important prognostic indicator for patients with pT2 gastric cancers who underwent curative gastrectomy. In the TNM staging system, subdivision of pT2 tumors should be undertaken routinely to detect gastric cancer patients who have a poor prognosis and to define patients more accurately in terms of their mortality after curative resection in accordance with the new 2010 AJCC TNM staging classification. This may also help as a guide to more appropriate therapy for tumors with subserosal invasion (old pT2b or new pT3).
Keywords: Gastric cancer; pT2 subcassification; Lymph node metastasis; Prognosis; PROGNOSTIC-FACTORS; SUBCLASSIFICATION; MUSCULARIS; CARCINOMA